Base mucronutrients and food groups consumption, associations with the risk of fatal cardiovascular disease development in people with type 2 diabetes: a prospective cohort study - O. D. Rymar; A. O. Shchetinina; S. V. Mustafina; G. I. Simonova; L. V. Shcherbakova; A. K. Kuntseviсh (Сибирский научный медицинский журнал, 2021)
Aim. To study the relation between the consumption of the main macronutrients and food groups with the risk of fatal outcomes from cardiovascular diseases (CVD) in people with newly diagnosed diabetes and those who are informed about type 2 diabetes mellitus (T2DM). Material and methods. This prospective analysis included 681 people (284 men and 397 women) with T2DM at baseline HAPIEE (Health, Alcohol and Psychosocial factors In Eastern Europe) 2003 (05) – December 31, 2018 and averaged 14.7 ± 0.7 years. There were 207 incident CV mortality during follow-up period (107 men, 100 women). The questionnaire on the presence of T2DM included information on the awareness of individuals about the presence of T2DM (“Did the doctor tell you that you have T2DM?”). The actual nutrition data included information on the consumption of 147 foods. The hazard ratio was estimated using Cox regression. Results and discussion. In men who aware of T2DM, the risk of developing a fatal CV event decreases with an increase in the consumption of “all-season” fruits (HR 0.413; 95 % confidence interval (CI) 0.234-0.786) and increases with an increase in the consumption of chicken eggs (HR 1.907 95 % CI 1.051-3.437), and alcohol (HR 1.031; 95 % CI 1.001- 1.061). In men who are unaware of T2DM, with an increase in nut consumption, the risk of developing fatal CV events decreases (HR 0.821; 95 % CI 0.679-0.992) and increases with increasing consumption of dairy products (HR 1.105; 95 % CI 1.000-1.221). In women aware of T2DM, consumption of white bread increases the risk (HR 1.489; 95 % CI 1.105-2.004), on the contrary, consumption of black bread reduces the risk of an undesirable outcome (HR 0.575; 95 % CI 0.424-0.818). Conclusions. In men who aware of T2DM, the most significant risk factors were the poor all-season fruits intake and excessive chicken eggs consumption. In women with type 2 diabetes, an increase in white bread consumption is of importance to increasing the risk of an undesirable CV outcome, and an increase in black bread consumption counts for reducing the risk.